Development Of Strategy Map And Measuring Corporate Performance With Sustainability Balanced Scorecard Approach (Case Study On Renewable Energy Consultant Services Company Pt Xyz) - Destianissa, Marsha; Pasaribu, Rina Djunita (Publisher Cv. Inara, 2024)
This study aims to develop a Strategy Map of PT XYZ based on the company's vision, mission, strategic goals and analyze the company's performance as measured using the Sustainability Balanced Scorecard (SBSC) method. The research method used is qualitative, which involves conducting in-depth interviews and analyzing company documents. According to the research results, the PT XYZ Strategy Map consists of a vision, mission, 17 company strategic goals and 34 measurement indicators. The company performance of PT XYZ in 2021 and 2022, measured by the 5 SBSC perspectives can be indicated as sufficient performance, which obtained a total scorecard of 0. Based on 34 measurement indicators, 13 obtained a good assessment, 13 obtained a poor assessment, 3 obtained a sufficient assessment, and 5 could not be calculated because the company did not have related numerical documents. In the future, PT XYZ needs to increase its efforts to improve company performance and improve company data management so that it is easier to identify the company's achievements or performance to a measurable extent. Further, PT XYZ needs to integrate sustainability goals that become the company's vision into the company's business strategy, one of which is using SBSC as a company performance measurement tool. In addition, PT XYZ needs to integrate its vision of contributing to sustainability development into the company's business strategy, one of which is the use of SBSC as a corporate performance measurement tool.